The Role And Significance Of Preparation Types In The Game Of Basketball - Toshpulatov S.K. (Euro Asian Journal Publishing, 2024)
This article provides basic information on the physical, technicaltactical, psychological, theoretical and proper organization of competition preparations in order to achieve high sportsmanship in the game of basketball and win competitions.
Keywords: Reaction; time; tool; methods